BAlN alloy for enhanced two-dimensional electron gas characteristics of GaN/AlGaN heterostructures. (4th September 2020) - Lin, Rongyu; Liu, Xinwei; Liu, Kaikai; Lu, Yi; Liu, Xinke; Li, Xiaohang
Abstract: Emerging wide bandgap BAlN alloys have potential for improved III-nitride power devices, including high electron mobility transistors (HEMTs). Yet, few relevant studies have been carried out. In this work, we have investigated the use of the B0.14 Al0.86 N alloy as part or the entirety of the interlayer between the GaN buffer and the AlGaN barrier in the conventional GaN/AlGaN heterostructure. The numerical results show considerable improvement of the two-dimensional electron gas (2DEG) concentration with small 2DEG leakage into the ternary layer by replacing the conventional AlN interlayer by either the B0.14 Al0.86 N interlayer or the B0.14 Al0.86 N/AlN hybrid interlayer. Consequently, the transfer characteristics can be improved. The saturation current can be enhanced as well. For instance, the saturation currents for HEMTs with the 0.5 nm B0.14 Al0.86 N/0.5 nm AlN hybrid interlayer and the 1 nm B0.14 Al0.86 N interlayer are 5.8% and 2.2% higher than that for the AlN interlayer when VGS −Vth = +3 V.